The Effects of Export Diversification on Macroeconomic Stabilization: Evidence from Korea - Jinsoo Lee; BOK-KEUN, YU (KDI Journal of Economic Policy, 2019)
This paper studies whether export diversification mitigated the negative effect of the global financial crisis on exports using the Korean case. Specifically, we use annual data on the exports of 24 Korean manufacturing industries from 2000 to 2016 and examine whether the negative effect of the crisis on exports was less prevalent in industries that were more diversified in terms of country and product. We also examine whether export competitiveness, as measured by the revealed comparative advantage index by industry, had a mitigating effect on trade during the crisis. In order to study these issues, we use panel regression with a fixed-effect model for 24 Korean manufacturing industries. From our empirical analysis, we find that country diversification weakened the negative impact of the global financial crisis on Korea’s exports, whereas neither product diversification nor export competitiveness did so.
Keywords: Export Diversification, Global Financial Crisis, Macroeconomic Stabilization